1998
DOI: 10.1021/bc9702157
|View full text |Cite
|
Sign up to set email alerts
|

Polycaprolactone-b-poly(ethylene Oxide) Block Copolymer Micelles as a Novel Drug Delivery Vehicle for Neurotrophic Agents FK506 and L-685,818

Abstract: Micelles formed from polycaprolactone-b-poly(ethylene oxide) (PCL-b-PEO) diblock copolymers were investigated as a novel drug delivery system. The affinity of the micelles for hydrophobic solubilizates was assayed by determining the partition coefficient for the lipophilic compound, pyrene, between the micelles and water; the partition coefficient was found to be on the order of 10(2). The Trypan blue and Alamar blue survival assays were used to assess the in vitro biocompatibility of the micelles with PC 12 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
225
2
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 273 publications
(237 citation statements)
references
References 28 publications
(46 reference statements)
8
225
2
2
Order By: Relevance
“…This high degree of biocompatibility of MePEG-b-PCL diblock copolymers was also reported by other groups in several different cell lines, including erythrocyte, breast cancer, pheochromocytoma, and cervical cancer cells. 3,28,29 The short-term-cytotoxicity study also suggested that the PCL19 and PCL104 copolymers did not cause a high degree of cell lysis, as indicated by low LDH release (Figure 2). Similar to PCL19 and PCL104 copolymers, both short-and long-term cell-viability assays demonstrated that the PCL5 copolymer did not cause cell death at concentrations up to 1% (w/v), suggesting that this copolymer is also highly biocompatible with MDCKII and MDCKII-MDR1 cell lines ( Figure 3A and B).…”
Section: Discussionmentioning
confidence: 90%
“…This high degree of biocompatibility of MePEG-b-PCL diblock copolymers was also reported by other groups in several different cell lines, including erythrocyte, breast cancer, pheochromocytoma, and cervical cancer cells. 3,28,29 The short-term-cytotoxicity study also suggested that the PCL19 and PCL104 copolymers did not cause a high degree of cell lysis, as indicated by low LDH release (Figure 2). Similar to PCL19 and PCL104 copolymers, both short-and long-term cell-viability assays demonstrated that the PCL5 copolymer did not cause cell death at concentrations up to 1% (w/v), suggesting that this copolymer is also highly biocompatible with MDCKII and MDCKII-MDR1 cell lines ( Figure 3A and B).…”
Section: Discussionmentioning
confidence: 90%
“…Because the peptide contains both hydrophobic and hydrophilic segments, we hypothesized that it could interact with the hydrophobic cargo and still have a good solubility in aqueous solution. Previous work showed that pyrene can be a good hydrophobic model drug because of its low water solubility (Ϸ6 ϫ 10 Ϫ7 M), well-defined fluorescence spectra, and well-established method to statistically analyze the transfer rate of pyrene into liposome vesicles (20)(21)(22)(23)(24)(25). We therefore used this system to measure our peptide-mediated delivery of pyrene into liposomes.…”
Section: Morphological Study By Atomic Force Microscopy (Afm)mentioning
confidence: 99%
“…The hydrophobic blocks form the core of the micelle, which is surrounded by the hydrophilic blocks, which form the outer shell (Zhang and Eisenberg, 1995). The inner core of the micelle creates a hydrophobic microenvironment for the nonpolar drug; while the hydrophilic shell provides a stabilizing interface between the micelle core and the aqueous medium (Allen et al, 1998). The drug delivery systems based on polymeric micelles are generally not stable and drug release is often very fast.…”
Section: Introductionmentioning
confidence: 99%